Ion D. Berindei - 150 years since birth (Confluenţe Bibliologice, 2022)
The article presents the work of the Romanian architect Ion D. Berindei (1871- 1928), describes the postage stamps put into circulation by Romfilatelie in honor of the commemoration of 150 years since the birth of this famous personality.